A Phenomenological Insight into Institutional and Value Shifts Among Minangkabau Women: Implications for Understanding Muslim Minority Dynamics - Yunarti, Sri; Sahid, Mualimin Mochammad; Dedi, Syahrial; Hesti, Kamila; Hasyiem, Lathifah (Jurnal Ilmiah Al-Syir'ah, 2025)
This article examines the shifting role of women in Minangkabau society, the world's largest matrilineal Muslim community, where contemporary dynamics challenge traditional institutional structures and value systems. This research analyzes how social mobility, migration, and institutional changes affect Minangkabau women's position as Bundo Kanduang, situating findings within comparative perspectives on matrilineal Muslim communities in majority and minority contexts. The research employed a phenomenological approach involving observation, in-depth interviews with 40 informants across five West Sumatra districts (Tanah Datar, Agam, Lima Puluh Kota, Padang Pariaman, Solok), and document analysis. Data interpretation centered on women's lived experiences to understand institutional and value transformation dynamics. Results reveal women's roles shifted from collective matrilineal responsibilities to nuclear family focus, driven by external factors (globalization, education, inter-ethnic marriage) and internal factors (value reinterpretation, institutional desacralization). Traditional institutions like Rumah Gadang and Bundo Kanduang organizations experienced functional decline. Comparative analysis demonstrates that Minangkabau women in majority Muslim contexts navigate internally-driven changes with substantial adaptive space for syncretic shariah-adat negotiation, while matrilineal Muslim minorities face intense external pressures from dominant patrilineal legal frameworks, resulting in accelerated institutional transformation with constrained individual agency. Role transformation results from complex global-local interactions, with adaptation mechanisms differing systematically between majority and minority contexts. These findings illuminate Islamic family law's differential flexibility across socio-political settings and provide crucial insights for developing culturally sensitive policies supporting matrilineal Muslim communities navigating modernization pressures globally.